12th North American Caribou Workshop, 2-5 November 2008, Happy Valley – Goose Bay, Newfoundland and Labrador, Canada. - Haugerud (editor in chief), Rolf Egil; Otto, Robert; Ellsworth (issue editors), Sabrina (Rangifer, 2011)
The 12th NACW was arranged at Happy Valley - Goose Bay 4-6 November 2008 with the theme "Integrating Understanding across Ecotypes". Approximately 140 people attended from Canada, United States, Norway, and Greenland. The 12th NACW included more than 70 oral and poster presentations.